Comparing the acute effects of shiftwork on mothers and fathers. (24th June 2021) - Tucker, P; Leineweber, C; Kecklund, G
Abstract: Background: Shift work may impact women more negatively than men due to the increased burden of coping with demanding work schedules while also undertaking more of the domestic chores, including childcare. Aims: To examine whether the combination of shift working and caring for children affects the sleep, fatigue and work–family conflict experienced by women more than it affects men. Methods: Using data from a survey of the Swedish working population, mixed linear regression models examined work schedule (daywork, shift work with nights, shift work without nights), gender and presence of children <13 years at home as predictors of sleep insufficiency, sleep disturbance, fatigue and work–family conflict, over up to three successive measurement occasions. Adjustments were made for age, education, full/part-time working and baseline year. Results: In fully adjusted models ( N = 8938), shift work was associated with insufficient sleep ( P < 0.01), disturbed sleep ( P < 0.01), fatigue ( P < 0.05) and work–family conflict ( P < 0.001). Interactions in the analyses of sleep disturbance ( P < 0.001) and work–family interference ( P < 0.05) indicated that among participants with no children, females reported more disturbed sleep and more work–family conflict than their male counterparts, irrespective of schedule; while among participants with children, female dayworkers reported more disturbed sleep than their male counterparts, and females working shifts without nights reported more work–family interference. Conclusions: Having young children did not exacerbate negative effects of shift work, in either men or women. This may reflect high levels of gender equality and childcare provision in Sweden.